STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN AKHLAK SISWA DI SMPIT IFLAHAH AT THOYYIBAH - Subhan Fadli; Novia Nasyomia (STKIP Pesisir Selatan, 2025)
Moral education plays a strategic role in shaping students' character, particularly in integrated Islamic schools that integrate Islamic values ​​into the learning process. Islamic Religious Education (PAI) teachers play a crucial role as the primary agents in instilling moral values ​​in students. This study aims to describe and analyze the strategies of Islamic Religious Education teachers in shaping students' morals at SMPIT IFLAHAH AT THOYYIBAH, as well as to identify supporting and inhibiting factors in their implementation. This study employed a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews, and documentation studies of PAI teachers and students. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques to ensure the validity of the research findings. The results showed that the strategy for shaping students' morals was carried out through habituating religious behavior, teacher role models, providing advice, and integrating Islamic values ​​into intracurricular and extracurricular activities. Furthermore, the use of technology and Islamic digital education also strengthens the internalization of students' moral values.